Morphological and functional analysis of colorectal cancer cell lines in 2D and 3D culture models - Seiichi Shinji; Yutaro Ogawa; Takeshi Yamada; Akihisa Matsuda; Kay Uehara; Yasuyuki Yokoyama; Goro Takahashi; Takuma Iwai; Toshimitsu Miyasaka; Shintaro Kanaka; Koki Hayashi; Yuuki Shichi; et al. (Scientific Reports)
Abstract The epithelial and mesenchymal features of colorectal adenocarcinoma (CRAC) cell lines were compared in two-dimensional (2D) and three-dimensional (3D) cultures. In 2D cultures, the three CRAC cell lines exhibited epithelial characteristics with high E-cadherin and low vimentin levels, whereas two exhibited mesenchymal traits with opposite expression patterns. In 3D cultures using low-attachment plates, mesenchymal cells from 2D cultures showed reduced vimentin mRNA levels. Morphologically, the five CRAC cell lines appeared similarly shaped in 2D culture but formed different structures in 3D culture. Epithelial DLD-1 and mesenchymal COLO-320 cells produced large granular spheres, whereas epithelial HCT-15 cells formed small solid spheres. Tubular structures were observed in epithelial CACO-2 and mesenchymal SW480 spheres. Desmosome-like structures developed in epithelial CRAC cells, whereas entosis was observed in CACO-2, HCT-15, and SW480 cells. The Ki-67-positive proliferating cell count varied in 2D and 3D cultures of epithelial cells but remained high and unchanged in mesenchymal cells. These findings suggest that while CRAC cells display distinct epithelial and mesenchymal properties in 2D cultures, they form diverse 3D structures, irrespective of these traits.